Unravelling the role of band‐offset landscape on the recombination zone dynamics in perovskite light‐emitting diodes. Issue 3 (19th December 2020) - Zhang, Jianfeng; Jiang, Le; Huang, Jincheng; Luo, Xi; Luo, Zhongming; Zhou, Dingjian; Kwok, Hoi‐Sing; Xu, Ping; Li, Guijun
Abstract: In recent years, impressive progress has been made in developing high‐performance perovskite light‐emitting diodes (PeLEDs) with efficiencies comparable to those of traditional organic light‐emitting diodes (OLEDs). It is convinced that the position of exciton recombination zone is crucial for the performance of the LEDs, however, the dynamics of the exciton recombination zone in PeLEDs and its influence on the performance of PeLEDs remain unclear. Herein, luminescent quantum‐dots (QDs) sensing layers with different energy band landscape and electric properties are introduced into PeLEDs as probers to investigate the position of recombination zone. Consequently, it is found that the band offset between the perovskite layer and the adjacent layer is vital to the position of recombination zone. Modulating the recombination zone towards the bulk of the emission layer helps to improve the device performance as well as the operational stability. Abstract : An emissive QDs layer is used to unravel the dynamics of the recombination zone in a perovskite LED . It is found that band‐offset landscape is crucial to the recombination zone. Modulating the recombination zone by different charge injection or interface layer elaborately, emission properties are improved as well as operational stability.